Homogeneous Polyporus Polysaccharide Inhibit Bladder Cancer by Resetting Tumor-Associated Macrophages Toward M1 Through NF-κB/NLRP3 Signaling - Liu, Chunping; He, Dongyue; Zhang, Shihui; Chen, Huiqi; Zhao, Jie; Li, Xiong; Zeng, Xing (Frontiers in Immunology, 2022)
Polyporus is an edible and medicinal fungus in the porus family of Basidiomycota, and its main active component is polysaccharide. In this study, we studied the polarization of macrophages induced by HPP（Homogeneous polyporus polysaccharide） in the bladder tumor microenvironment and explored its anti-bladder cancer mechanism. First, we established a BBN bladder cancer rat model and compared it with human bladder cancer specimens to confirm the success of the model. After intervention with polyporus extract and polysaccharide, the pathological condition of BBN bladder cancer rats was improved, which may be related to the regulation of the bladder tumor inflammatory microenvironment, but the material basis of the effect is not clear. Therefore, we further extracted a new polysaccharide from polyporus, which was proven to have an α-(1→ 4)-linked D-galactan backbone. To simulate the bladder tumor microenvironment, we cultured macrophages with T24 cell supernatant to establish a tumor-associated macrophage model and further verified the anticancer mechanism of HPP. The results showed that HPP promoted the polarization of tumor-associated macrophages (TAMs) toward the M1 subtype, possibly through the NF-κB/NLRP3 pathway. By inhibiting the NF-κB signaling pathway with SC-75741, the tendency of HPP to activate NF-κB/NLRP3 and promote the secretion of inflammatory factors was reversed. Therefore, our study suggested that HPP regulates TAM polarization to improve the tumor inflammatory microenvironment, possibly through the NF-κB/NLRP3 signaling pathway. HPP may be a potential therapeutic agent for bladder tumors.